Parasitism of the nasal mite Sternostoma tracheacolum Lawrence, 1948 (Mesostigmata: Rhinonyssidae) in captive birds in Brazil - Bassini-silva, Ricardo (2019)
Abstract Nasal mites (Mesostigmata: Rhinonyssidae) are obligatory endoparasites of birds, and the resulting parasitism can be harmful to the host’s respiratory system. The nasal mite Sternostoma tracheacolum Lawrence has caused significant respiratory issues, including serious injuries that possibly cause death of the host. In this study, we report two cases of captive birds parasitized by S. tracheacolum. The first case is a histopathological description of S. tracheacolum parasitizing the Gouldian Finch (Chloebia gouldiae) in the southeast region of Brazil, that showed partially or totally absence of the characteristic respiratory epithelium in trachea lumen. The other describes, for the first time, the parasitism of this species in a canary (Serinus canaria) in the northeast region of the country.